Exploring Artificial Intelligence In Islamic Pedagogy Through a Systematic Literature Review For Cognitive and Character Education - Iqbal, Muhammad; Maulana, Hanif (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
The rapid advancement of Artificial Intelligence (AI) technology presents transformative opportunities for education, particularly in the context of Islamic pedagogy. This systematic literature review explores the integration of AI into Islamic education, focusing on its potential to support character and cognitive development while aligning with Islamic values. The study identifies critical research gaps, analyzes existing literature, and synthesizes findings to propose actionable insights for future advancements. Results reveal that AI can personalize learning experiences, enhance critical thinking, and integrate moral and spiritual principles into the educational process. However, challenges such as ethical concerns, data privacy, and the need for localized AI solutions remain significant barriers. The findings underscore the importance of a holistic approach, combining intellectual, emotional, and spiritual dimensions in education. Recommendations include the development of AI-based curricula aligned with Islamic values, teacher training programs, and ethical frameworks to ensure the responsible application of AI in Islamic education. This research contributes to the growing body of knowledge on AI in education and provides a foundation for further exploration in integrating technology with Islamic pedagogy to enhance educational outcomes.